On designing a distributed event‐triggered output feedback consensus protocol for nonlinear multiagent systems - Li, Hanfeng; Xia, Shengxiang; Mu, Rui; Zhang, Xianfu (International journal of robust and nonlinear control, 2021)
In this article, the leader–follower consensus problem is considered for a class of nonlinear multiagent systems with event‐triggered inputs. A novel time‐varying gain compensator is designed for each follower by only utilizing the output information of the follower and its neighbors. Based on a time‐varying threshold strategy and a directed communication topology, a distributed event‐triggered output feedback controller is designed for each follower. It is proved by the Lyapunov theory that the leader–follower consensus of the multiagent systems is achieved and the Zeno‐behavior is avoided. Compared with the existing results, it is the first time that a time‐varying gain control algorithm is proposed for the multiagent systems subject to event‐triggered inputs. The effectiveness of the proposed consensus protocol is validated by the chemical reactor systems.